The Manufacturing of Low Temperature Measuring Devices Using a PT-100 Sensor Based on ATmega328 Microcontroller - Yusuf, Bhakti Hardian; Satriya Wibawa, I Made; Putra, I Ketut (BULETIN FISIKA; Vol 21 No 1 (2020): BULETIN FISIKA, 2020)
A low temperature measuring device has been successfully developed using a microcontroller-based PT-100 sensor ATmega328. The temperature is measured using a PT-100 sensor, as the main processor using the ATmega 328 microcontroller, and the measured temperature is displayed on a 2x16 LCD. The results of the calibration at a temperature of 77 - 300 K against the reference measuring instrument obtained that, the ratio of the measured temperature between the reference measuring instrument and the measuring instrument made was 0.9893 ± 3.69 K and the coefficient of determination R2 = 0.9987. This indicates that the measurement results of the measuring instruments made have an accuracy level of 98.93% and a precision of 99.87%. Keywords: Low temperature, PT-100 Sensor, ATmega328 Microcontroller, LCD 2x16